2013
DOI: 10.1155/2013/858946
|View full text |Cite
|
Sign up to set email alerts
|

STAT6 siRNA Matrix-Loaded Gelatin Nanocarriers: Formulation, Characterization, andEx VivoProof of Concept Using Adenocarcinoma Cells

Abstract: The clinical utility of siRNA therapy has been hampered due to poor cell penetration, nonspecific effects, rapid degradation, and short half-life. We herewith proposed the formulation development of STAT6 siRNA (S6S) nanotherapeutic agent by encapsulating them within gelatin nanocarriers (GNC). The prepared nanoformulation was characterized for size, charge, loading efficiency, release kinetics, stability, cytotoxicity, and gene silencing assay. The stability of S6S-GNC was also assessed under conditions of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 90 publications
0
23
0
Order By: Relevance
“…31 Additionally, another study reported that PEBP4 inhibition in cervical cancer is associated with higher tumor aggressive behavior and resistance to cisplatin therapy. 32 Our finding showed that downregulation of PEBP4 induces EMT and contributes to cisplatin resistance. We further establish miR-15b-PEBP4 as another important pathway regulating EMT and chemoresistance of lung adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…31 Additionally, another study reported that PEBP4 inhibition in cervical cancer is associated with higher tumor aggressive behavior and resistance to cisplatin therapy. 32 Our finding showed that downregulation of PEBP4 induces EMT and contributes to cisplatin resistance. We further establish miR-15b-PEBP4 as another important pathway regulating EMT and chemoresistance of lung adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 58%
“…30,31 In gastric cancer cells, miR-15b promotes cell growth and metastasis both in vitro and in vivo. 32 In addition, it could regulate endothelial differentiation of breast cancer stem-like cells. 33 Moreover, miR-15b plays an important role in mediating drug resistance by targeting multiple drug-resistance-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…DTX-CNTs exhibited superior drug release profile especially at acidic pH corresponding to conditions existing at tumorous site. So, carboxylated nanotubes present themselves as potential cargo for anticancer agents and can bring upheaval in the field of cancer therapy but in vivo studies shall be essential to have better insight of their toxicological profile (54)(55)(56)(57). Although, higher hemolytic toxicity of naked CNTs and dendrimer mandates their surface modification by some appropriate strategy (like PEGylation).…”
Section: Resultsmentioning
confidence: 99%
“…The natural polymers that have commonly been used for preparation of polymeric nanoparticles are albumin, chitosan, dextran, gelatin, lectins, and sodium alginate (Tekade R.K. and Chougule M.B., 2013, Tekade R.K. et al, 2014, Youngren S.R. et al, 2013).…”
Section: Non-viral Delivery Of Sirna To the Lungmentioning
confidence: 99%